2021
DOI: 10.1186/s12909-021-02621-y
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods study to evaluate the impact of a student-run clinic on undergraduate medical education

Abstract: Background The purpose of this study was to evaluate the extent to which a longitudinal student-run clinic (SRC) is meeting its stated learning objectives, including providing critical community services and developing physicians who more fully appreciate the social factors affecting their patients’ health. Methods This was a mixed methods program evaluation of an SRC at Mayo Clinic Alix School of Medicine (MCASOM). A survey was conducted of medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 23 publications
(8 reference statements)
0
22
0
Order By: Relevance
“…Table 2 provides an overview of each SDOH curriculum, and its primary feature. Of the eight curricula included in the review, six were from medical schools in the United States [ 11 16 ], one from the United Kingdom (U.K.) [ 17 ], and one from Israel [ 18 ]. Seven programs were aimed at medical students [ 11 , 12 , 14 18 ], and only one curriculum was an inter-professional program covering medical students and other health professionals, including medical, nursing, pharmacy school, public health students, and social work students [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 provides an overview of each SDOH curriculum, and its primary feature. Of the eight curricula included in the review, six were from medical schools in the United States [ 11 16 ], one from the United Kingdom (U.K.) [ 17 ], and one from Israel [ 18 ]. Seven programs were aimed at medical students [ 11 , 12 , 14 18 ], and only one curriculum was an inter-professional program covering medical students and other health professionals, including medical, nursing, pharmacy school, public health students, and social work students [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Didactic online or in-person 2.Experiential Learning 3. Reflective assignments and presentations • Inter-professional learning experience • Critical thinking • Community engagement and exposure to diversity in realistic situations • Recognition of the community priorities and the impact of health outcomes • Reflective skills 15 14.5 Rockey et al 2021 [ 11 ] United States (Mayo Clinic Alix School of Medicine) Student-run clinic Mandatory The clinic runs weekly over two and half days Students take an initial assessment of the patients, then present to the physician, where he prescribes any further investigation or prescriptions needed Full year for Second-year medical students Experiential Learning • Community engagement and exposure to diversity in realistic situations • Inter-professional experience and working with a multidisciplinary team • Recognition of the community priorities and the impact of health outcomes • Understanding the responsibilities of healthcare physicians towards patient's care • Basic health screening skills 12.5 13 Sagi et al 2020 [ 18 ] Israel (Azrieli Faculty of Medicine at Bar-Ilan University) Etgar course * Mandatory A full-day introductory session Four tutorials within the clinical rotations Home visits within one week of discharge and follow up the phone within two weeks of the home visit Reports for their home-visits experience Lectures and simulation-based training Tutorials include case simulation for patients to help recognise the SDOH Home-visit post-discharge, using a semi-structured report to evaluate the barriers for healthcare in underprivileged areas Planning a discharge plan and liaison with any services required Full year for third and the fourth-year students 1. Didactic 2.Experiential Learning • Realistic care experience • Early recognition of the healthcare equity barriers through home visits • Experience of community service with the broader context of SDOH • Reflective skills 12.5 12 Moffett et al 2019 [ 12 ] United States (New Jersey ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, education and intervention strategies for patients at SRCs were often aimed at poor hygiene, limited clean water, etc. [14]. NCDs are difficult to address in any population as recent studies have shown that education is less effective at changing behavior than implementing changes in local policies and laws [15].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to real-life clinical environments through clinical placement is integral to preparing healthcare students for practice (Atakro et al, 2019). Authentic environments such as those provided within student-led healthcare services allow students to improve their understanding of the social determinants of health and other barriers to healthcare access (Rockey et al, 2021), while contributing to the development of competency within the healthcare systems they intend to practise in (Froberg et al, 2018). However, to substantiate student-led healthcare services as quality providers of clinical education and promote their use as clinical placements, student-led healthcare services must be first substantiated as quality providers of healthcare.…”
Section: Introductionmentioning
confidence: 99%